2012
DOI: 10.1111/j.1463-1318.2012.03046.x
|View full text |Cite
|
Sign up to set email alerts
|

How far has the pendulum swung in the surgical management of sigmoid volvulus? Experience from the KwaZulu‐Natal Teaching Hospitals and review of the literature

Abstract: The clinicopathological picture of sigmoid volvulus resembles that in the rest of Africa in that it affects predominantly young African males. The level of the twist is at the pelvic brim. The timing of surgery, the type of anastomosis and the viability of the bowel does not influence outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…An uncomplicated sigmoid volvulus can be untwisted without opening the abdomen, by gently inserting a well-lubricated large rubber tube through an instrument (a proctoscope) inserted into the rectum. Overall survival should exceed 80 percent (Mnguni and others 2012;Nuhu and Jah 2010).…”
Section: Types Of General Surgical Emergenciesmentioning
confidence: 99%
“…An uncomplicated sigmoid volvulus can be untwisted without opening the abdomen, by gently inserting a well-lubricated large rubber tube through an instrument (a proctoscope) inserted into the rectum. Overall survival should exceed 80 percent (Mnguni and others 2012;Nuhu and Jah 2010).…”
Section: Types Of General Surgical Emergenciesmentioning
confidence: 99%
“…The non-resection procedures of sigmoidopexy and recto-sigmoidoplasty do not require bowel preparation with lower morbidity and mortality rates at first incidence. However, the recurrence rate is still very high, ranging from 45% to 71% [9] . Where a detorsion fails, and there are signs of colonic gangrene, sigmoid resection and Hartmanns' procedure with a temporary colostomy with a mucus spout would be done to avoid the high mortality associated with primary anastomosis in this situation [6,10] .…”
Section: Research Articlementioning
confidence: 99%
“…The mortality rate was twelve (30%) from various post-operative morbidities, especially peritonitis, septicemia, respiratory failure; Table 2. The rest died of consequences of multi-organ failures (MOF) [9] .…”
Section: Treatment Outcomementioning
confidence: 99%
“…Mnguni et. al, [6] reported that SV predominately affected young African males and found that the timing of surgery, the type of anastomosis and the viability of the bowel did not influence surgical outcomes in 135 patients (122 males; with a mean age of 39.3 years; SD ± 17 years). Complications and mortality occurred in 14% and 17% of the study patients, respectively.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A search through Medline, PubMed, Cinahl, and Ovid databases revealed that only16 reported SV studies were conducted in non-Western settings [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]25]. Only one of these studies examined lengths of stay (LOS) or sequelae associated with LOS and treatment.…”
Section: Review Of the Literaturementioning
confidence: 99%